"2D or not 2D": Shape-programming polymer sheets. (January 2016) - Liu, Ying; Genzer, Jan; Dickey, Michael D.
Abstract: This review summarizes progress toward programming two-dimensional (2D) polymer sheets which respond to a variety of external stimuli to form three-dimensional (3D) shapes or topographical features on macroscopically planar sheets. Shape programming strategically adds value or function to 2D sheets, films, or coatings that can be created inexpensively. 2D substrates are common form factors that are compatible with ordinary 2D patterning techniques ( i.e., inkjet, photolithography, roll-to-roll printing) and may be stored, packed, and shipped efficiently. Polymer materials are attractive due to their flexibility, light weight, low price, and compatibility with high throughput processing. This review highlights strategies for triggering shape change in planar polymeric materials. The strategies are divided into four broad categories: (1) 2D substrates with latent topography "programmed" using conventional microfabrication, (2) 2D substrates that form topography due to imposed or self-generated stress, (3) 2D substrates that form 3D shapes by out-of-plane bending, and (4) 2D substrates that use "hinges" to achieve out-of-plane folding. The review highlights all strategies while focusing primarily on last two approaches.